Gentamicin Induced Hepatotoxicity: An approach of Hepatoprotecion by Garlic - Mishra, R.; Shrivastava, V. K. (International Journal of Scientific Research in Biological Sciences, 2018)
Gentamicin hepatotoxicity is a major clinical drawback. This investigation was performed to scrutinize the effect of garlic extract as a herbal antidote on liver toxicity after treatment with gentamicin in male albino rats. Gentamicin is a widely used anti-infective broad-spectrum antibiotic of aminoglycoside family. Side effects of gentamicin medication occur due to free radical formation. Garlic, the bulb of Allium sativum, is universally used as a spice and also known for its medicinal and antioxidant properties. Forty adult male albino rats, Rattus norvegicus were randomly classified into four groups of ten each. Group 1 received 0.9% normal saline orally per day and served as control while group 2 received gentamicin intramuscularly per day, however group 3 received both gentamicin intramuscularly per day and garlic extract orally per day, while group 4 received only garlic extract orally per day for 30 and 60 days respectively. Gentamicin caused various structural and functional changes in hepatic cell, increased glutamate pyruvate transaminase (GPT), glutamate oxaloacetate transaminase (GOT), acid phosphatase (ACP), alkaline phosphatase (ALP) and decreased total protein and creatinine level. Co-administration of garlic extract to rats ameliorates the gentamicin toxicity at some extent in hepatic cells as shown in the results of biochemical, enzymological and histopathological studies. Garlic extract was effective in recovering the level of hepatic enzymes, biochemical markers and histological alterations; hence, it may be concluded that garlic reduces the gentamicin hepatotoxicity in rats.